Gut microbiota is associated with metabolic health in children with obesity. Issue 8 (August 2022) - Alcazar, M.; Escribano, J.; Ferré, N.; Closa-Monasterolo, R.; Selma-Royo, M.; Feliu, A.; Castillejo, G.; Luque, V.; ,; Closa-Monasterolo, R.; Escribano, J.; Luque, V.; et al.
Summary: Background and aims: We aimed to describe and characterize the gut microbiota composition and diversity in children with obesity according to their metabolic health status. Methods: Anthropometry, Triglycerides, HDL cholesterol, HOMA-IR, and systolic and diastolic blood pressure (SBP, DBP) were evaluated (and z-score calculated) and faecal samples were collected from 191 children with obesity aged from 8 to 14. All children were classified depending on their cardiometabolic status in either a "metabolically healthy" (MHO; n = 106) or "metabolically unhealthy" (MUO; n = 85) group. Differences in gut microbiota taxonomies and diversity between groups (MUO vs MHO) were analysed. Alpha diversity index was calculated as Chao1 and Simpson's index, and β-diversity was calculated as Adonis Bray–Curtis index. Spearman's correlations and logistic regressions were performed to study the association between cardiometabolic health and the microbiota. Results: Children in the MUO presented significantly lower alpha diversity and richness than those in the MHO group (Chao1 index p = 0.021, Simpson's index p = 0.045, respectively), whereas microbiota β-diversity did not differ by the cardiometabolic health status (Adonis Bray–Curtis, R 2  = 0.006; p = 0.155). The MUO group was characterized by lower relative abundances of the genera Christensenellaceae R7 group (MHO:1.42% [0.21–2.94]; MUO:0.47% [0.02–1.60], p < 0.004), and Akkermansia (MHO:0.26% [0.01–2.19]; MUO:0.01% [0.00–0.36], p < 0.001) and higher relative abundances of Bacteroides (MHO:10.6% [4.64–18.5]; MUO:17.0% [7.18–27.4], p = 0.012) genus. After the adjustment by sex, age, and BMI, higher Akkermansia (OR: 0.86, CI: 0.75–0.97; p = 0.033), Christensenellaceae R7 group (OR: 0.86, 95% CI: 075–0.98; p = 0.031) and Chao1 index (OR: 0.86, CI: 0.96–1.00; p = 0.023) represented a lower risk of the presence of one or more altered cardiovascular risk factors. Conclusion: Lower proportions of Christensenellaceae and Akkermansia and lower diversity and richness seem to be indicators of a metabolic unhealthy status in children with obesity.